Shape-stabilized phase change material preparation for thermal energy storage application - Nicholas, Ahmad Fariz; Hussein, Mohd Zobir; Zainal, Zulkarnain; Khadiran, Tumirah (2018)
This work was conducted to see the behavior of n-octadecane PCM towards different palm kernel shell activated carbon (PKSAC) prepared as shape-stabilized phase change material (SSPCM) for thermal energy storage (TES) application. The different PKSAC was identified from different amount of H3PO4 treatment given to palm kernel shell from 0, 5, 10, 20, 30 and 40% before activation. The impregnation of n-octadecane with the different PKSAC produced SSPCMs that expressed different physico-chemical characteristics. The BET surface area shows the obvious changes of value before and after impregnation which proves that the PKSAC is very suitable framework for the n-octadecane. The most obvious changes show in the graph is C20 by having the highest surface area compared to the others which is 1169 m2g-1 and decreased to 2 m2g-1. The X-ray diffractometer, field emission scanning electron microscope and FESEM images prove that the n-octadecane was successfully impregnated into the pores of AC without chemical interaction between the AC and n-octadecane. The SSPCM nanocomposite shows that the PKSAC is thermally good framework material for noctadecane observed by raman spectroscopy, TGA/ DTG thermal analysis, differential scanning calorimeter and leakage study.